The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1177/002215549804600205
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron Microscopic Characterization of Human Dermal Lymphatic Microvascular Endothelial Cells: Differential Expression of CD31, CD34, and Type IV Collagen with Lymphatic Endothelial Cells vs Blood Capillary Endothelial Cells in Normal Human Skin, Lymphangioma, and Hemangioma In Situ

Abstract: We performed a comparative investigation of the immunomorphological characteristics of lymphatic and blood microvascular endothelial cells in normal human skin, cutaneous lymphangiomas, and hemangiomas, employing a pre-embedding immunogold electron microscopic technique. We stained for cell membrane proteins that are commonly used for light microscopic characterization of blood endothelial cells. With blood microvascular endothelial cells, we observed uniform labeling of the luminal cell membranes with monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
106
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 36 publications
12
106
0
2
Order By: Relevance
“…Double staining for CD31 and LYVE-1 showed that a small population of cells in the periphery was doubly positive for both (Fig. 4B), consistent with previous findings (26,27). Importantly, E7080 treatment dramatically inhibited the numbers of CD31-and LYVE-1-positive cells (Fig.…”
Section: E7080 Inhibition Of Angiogenesis and Lymphangiogenesis In Mesupporting
confidence: 89%
“…Double staining for CD31 and LYVE-1 showed that a small population of cells in the periphery was doubly positive for both (Fig. 4B), consistent with previous findings (26,27). Importantly, E7080 treatment dramatically inhibited the numbers of CD31-and LYVE-1-positive cells (Fig.…”
Section: E7080 Inhibition Of Angiogenesis and Lymphangiogenesis In Mesupporting
confidence: 89%
“…4A-C). CD31 (PECAM-1, platelet endothelial cell adhesion molecule-1) is a marker of both BECs and LECs, and is also present on leukocytes of the periphery (Sauter et al, 1998). The leukocyte common antigen CD45, a transmembrane glycoprotein with a molecular weight of 180 -220 kDa, is a marker for cells of hematopoietic origin except for erythrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Several different negative controls are currently used in the different studies, ranging from isotype specific antibodies labeled with the same colors as the specific antibodies (8)(9)(10), addition of no antibodies at all to see the autofluorescence of the cells, to the fluorescence minus one (FMO) strategy [reviewed in (11)]. Another factor complicating the characterization of EPCs is the fact that the expression of the often used stem cell marker CD34 is not only restricted to stem cells, but is also expressed on mature microvascular endothelial cells (12,13). Therefore, CD133, a more immature hematopoietic stem cell marker that is absent on mature endothelial cells and monocytic cells (14) was introduced as a better marker for EPCs.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%